2018
DOI: 10.1016/j.chom.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Microbes Induce Serum IgA Responses that Protect against Polymicrobial Sepsis

Abstract: Serum immunoglobulin A (IgA) antibodies are readily detected in mice and people, but the mechanisms underlying the induction of serum IgA and its role in host protection remain uncertain. We report that select commensal bacteria induce several facets of systemic IgA-mediated immunity. Exposing conventional mice to a unique but natural microflora that included several members of the Proteobacteria phylum led to T cell-dependent increases in serum IgA levels and the induction of large numbers of IgA-secreting pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
191
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(214 citation statements)
references
References 53 publications
19
191
0
1
Order By: Relevance
“…Surprisingly, this work revealed that while the vast majority of plasma cells arise coincident with the GC reaction, most memory B cells appear to arise much earlier including before GCs were detected 40. 42 Therefore, while IgG-secreting plasma cells clearly dominate responses to immunization with exogenous T-dependent antigens, other pathways may also be at play.Interestingly, we recently reported that, in mice that were not intentionally immunized, upwards of 40% of bone marrow plasma cells secrete IgM, with another 40% or more actively secreting IgA 47. This observation is consistent with the other work showing that long-lived IgM + memory B cells can form via a GCindependent pathway.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Surprisingly, this work revealed that while the vast majority of plasma cells arise coincident with the GC reaction, most memory B cells appear to arise much earlier including before GCs were detected 40. 42 Therefore, while IgG-secreting plasma cells clearly dominate responses to immunization with exogenous T-dependent antigens, other pathways may also be at play.Interestingly, we recently reported that, in mice that were not intentionally immunized, upwards of 40% of bone marrow plasma cells secrete IgM, with another 40% or more actively secreting IgA 47. This observation is consistent with the other work showing that long-lived IgM + memory B cells can form via a GCindependent pathway.…”
supporting
confidence: 90%
“…63 Here we return to the layered immune system hypothesis. 47 Together these observations suggest that the IgA repertoire consists of multiple stable layers that collectively target and continuously regulate the composition of the bacterial microbiota. 72 Remarkably, 70% of these antibodies bound a diverse pool of commensal bacteria derived from the small intestine, suggesting that a large fraction of the IgA repertoire targets conserved molecular structures common to a variety of bacterial taxa.…”
Section: S Tab Le G Ermline-en Coded Antibody Repertoire S?mentioning
confidence: 96%
“…3C). In light of the tremendous impact of altered microbiota on the outcome of CLP sepsis (Wilmore et al, 2018), it will be interesting to examine whether Gpx4 deficiency causes microbiome variation in independent studies.…”
Section: Resultsmentioning
confidence: 99%
“…highlight the capacity of the mucosal immune interaction to affect systemic antibody response during homeostasis. The ability of the mucosal immune system to co‐operate with systemic immunity in a homeostatic context is further highlighted by increased levels of T‐dependent serum IgA in response to certain commensals in the gut and induction of IgA‐secreting plasma cells in the bone marrow . Furthermore, clonal relationships between gut IgA plasma cells and memory cells in the spleen as well as splenic IgM memory subsets with antibacterial specificities sustained from persistent mucosal responses have been described .…”
Section: Microbiota‐driven or Maintained Memory Antibody Responsesmentioning
confidence: 99%